The emancipatory promise of participatory water governance for the urban poor: Reflections on the transition management approach in the cities of Dodowa, Ghana and Arusha, Tanzania. Issue 4 (2nd October 2018) - Nastar, Maryam; Abbas, Shabana; Aponte Rivero, Carlos; Jenkins, Shona; Kooy, Michelle
ABSTRACT: There has been widespread recognition in the Global South of the role of participatory governance approaches to urban development in responding to citizens' immediate concerns. However, critiques note that participatory initiatives are often avenues for the political and economic elite to ensure their interests and profits, rather than improving the livelihoods in non- serviced urban peripheries. This article investigates how transition management (TM), as a promising participatory governance framework, can be implemented effectively to improve access to water for disadvantaged groups. First, we highlight lessons learnt from the TM applications in urban and water sectors. Second, we draw on empirical data from low-income urban areas in Ghana and Tanzania to bring the importance of social relations to the fore. By employing open-ended interviews, following the water points and conducting narrative walks, we identify three precautions that need to be addressed through adaptations of the TM approach in order to achieve the emancipatory promises of participatory governance models. In suggesting some guidelines for facilitators and active groups in participatory arenas, we discuss the importance of power dynamics in the communities, potentials and shortcoming of reflexive governance processes, and the need for capacity-building in transition teams.